PENGARUH PEMBANGUNAN GRAND MALL TERHADAP PENDAPATAN UMKM DI KOTA PALU (Analisis Ekonomi Syariah) - Sitti Aisyah; Juliastuti Juliastuti (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2015)
Economic globalization also have an impact on the influx of foreign and local ivestor (inside and outside of Palu). It is undeniable that the modern market today has become the demands and consequences of modern lifestyle that developed in the community. This research is a quantitative research. The study, using statistics to help analyze the data obtained in the field in which data is numeric or qualitative data in numbers. Furthermore, researchers in analyzing them also through Islamic economic approach, approach is based on the provisions of Islamic sharia economy related to economic development in order to achieve the objectives of sharia economic welfare of the people (Falah). Based on the results of the study showed that the presence of the Grand Mall greeted positively by SMEs even as Icon Palu city tour. Results are shown on several tables of data processed such that a positive response strongly agree and agree to 70% of the respondents. The influence of the presence of Grand Mall on revenue SMEs cause competition. But competition is meant fastabiqu al khairah positive competition (competing in goodness) as respondents that the presence of the Grand Mall can trigger the micro, small and medium enterprises to improve service, quality and innovation